Endometrial spatio-temporal image correlation (STIC) and prediction of outcome following assisted reproductive treatment. (August 2016) - Polanski, Lukasz T.; Baumgarten, Miriam N.; Brosens, Jan; Quenby, Siobhan; Campbell, Bruce; Martins, Wellington; Raine-Fenning, Nick
Abstract: Objective: The aim of this study was to correlate manual and spherical endometrial spatio-temporal image correlation (STIC) vascularity indices with assisted reproductive treatment (ART) outcomes. Study design: STIC ultrasound assessments of the endometrium were carried out at three time-points in 127 women in a prospective observational study. Results: Biochemical pregnancy rate was 69% (88/127), with a biochemical and clinical pregnancy loss of 17%. Endometrial STIC vascularity indices in the assessed time-points did not differ between subjects who achieved a clinical pregnancy and those who did not ( P > 0.05). For first trimester miscarriage, minimal manual vascularization index (VI) at oocyte collection (cut-off value ≥0.7; sensitivity 80.0% and specificity 68.1%) demonstrated the highest area under the curve (AUC) of 0.8. Conclusion: In summary, STIC modality is not a useful tool to predict ART outcome, however manual STIC analysis of endometrial vascularity seems to be more accurate in predicting first trimester pregnancy loss.